Benefit of sleep study in all patients with atrial fibrillation and BMI> 28, 0 Kg/m2 before catheter ablation. (19th May 2022) - Antunes Coelho, R; Parreira, L; Farinha, J; Esteves, A; Pinheiro, A; Ferreira, J; Quintal, J; Amador, P; Marinheiro, R; Mesquita, D; Caria, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Main funding source(s): None Background: Sleep apnea is a known risk factor for atrial fibrillation recurrence after catheter ablation. Despite this, in recent atrial fibrillation guidelines, it is unclear in which patients to test sleep apnea before catheter ablation. Purpose: Evaluate if body mass index (BMI) has a good discriminative power to predict sleep apnea in patients with atrial fibrillation proposed to catheter ablation. Methods: We retrospectively studied 160 consecutive patients undergoing catheter ablation of paroxysmal or persistent atrial fibrillation in our institution. We evaluated recurrence of atrial fibrillation after catheter ablation and analysed diagnosis of sleep apnea, body mass index, treatment with CPAP, echocardiographic findings (indexed volume of left atrium and left ventricular ejection fraction), cardiovascular risk factors and other comorbidities and clinical characteristics. Receiver operator characteristics (ROC) curve and area under the curve (AUC) were obtained to determine the discriminative power of body mass index as predictor of sleep apnea. Optimal cut-point value was obtained (Youden index) and patients were divided according to this value. Results: During a mean follow-up time of 22, 8 ± 19, 9 months, 46 patients (28, 8%) had atrial fibrillation recurrence and none died. The recurrence was associated with hypertension, alcohol habits and untreated sleep apnea (HR 3, 74; 95% CI 1, 89-7, 42; p <0, 001). Optimal cut-point value for predicting sleep apnea in patients with atrial fibrillation proposed to catheter ablation was BMI of 28, 0 Kg/m2 (AUC 0, 733, p = 0, 001, 95% CI 0, 640-0, 827). The group of patients with BMI of 28, 0 Kg/m2 had a 4-fold increased risk of sleep apnea (OR 3, 95, 95% CI 1, 85-8, 42, p =0, 001) and 2-fold risk of atrial fibrillation recurrence (HR 1, 96; 95% CI 1, 10-3, 51; p = 0, 023). Conclusions: In this group of patients undergoing catheter ablation of atrial fibrillation, a BMI ≥ 28, 0 Kg/m2 was independent predictor of sleep apnea and recurrence of atrial fibrillation after catheter ablation. In patients with atrial fibrillation proposed to catheter ablation and BMI ≥ 28, 0 Kg/m2 is reasonable to do a sleep study before catheter ablation.